PROFIL BERPIKIR SISWA SMP DALAM MEMECAHKAN BANGUN RUANG LIMAS BERDASARKAN TEORI BRUNER - Nirawati, Lia Septy; Cahyono, Heri (Universitas Muhammadiyah Semarang, 2019)
This study aims to determine the profile of students' thinking in solving mathematical problems and to find out the results of the application of Brunerd's theory in solving the problem of building a Limas room in junior high school students.Retrieval Techniques The subjects in this study were seen from the results of tests with high, medium, low categories. High categories were seen from the test results if the answers to the tests were all correct, the categories were seen from the test results if the answers to the tests still had errors, while the categories were low seen from the test results if the answer to the test is still wrong. This technique is used because researchers have a specific purpose for several considerations, namely to find out whether the application of bruner theory can be applied in mathematics subjects, considering that mathematics is considered a difficult subject for students. The subjects of this study were 6 students. Data collection techniques in this study used test, interview and documentation methods while the data validity techniques in this study used triangulation techniques which included 3 elements, namely sources, methods, theories. In this study researchers used data analysis techniques with 3 components, namely: data reduction, data presentation, conclusion drawing.The results showed that subjects with a high category tended to have high-thinking profiles, they had no difficulty in doing tests and interviews. The subjects with the medium category were more likely to have thinking profiles, while they had a little difficulty in doing tests and interviews, while the subjects with the lower category were more likely to have low-thinking profiles, they had difficulty doing tests and interviews. This is what causes a difference between them. Based on the discussion, it can be concluded that junior high school students in their profile think in solving problems in the building of a limiter junior high school students are able to describe the building of Limas space means that SMP students are able to understand pyramid material shown to the sensitivity of students in learning to build Limas space so that junior high school students in their imagination are able to mention 1 example of a pyramid building and all junior high school students are able to mention the types of Limas indicated by the independence of junior high school students who are able to mention various types of building> 1 in terms of bases, and junior high students are able to say> 1 element the building elements of the Limas space means that junior high school students are able to understand the pyramid material shown to the sensitivity of junior high school students to be able to mention the Limas parts properly and correctly.